Symptoms of anxiety and depression associated with steroid efficacy and clinical outcomes in patients with inflammatory bowel disease - Duan, Shihao; Yang, Yi; Cao, Yubin; Chen, Pingrun; Liang, Chang; Zhang, Yan (Frontiers in Psychiatry, 2023)
Background: Anxiety and depression symptoms are very common in patients with inflammatory bowel disease (IBD). We aimed to explore the impact of anxiety and depression on the efficacy of medications, as well as IBD-related poor outcomes. Method: This was a prospective longitudinal observational study. Hospital Anxiety and Depression Scale was used to assess anxiety and depression symptoms. Logistic regression analyses were used to assess the association between anxiety/depression and the response to different medications. Kaplan–Meier survival analysis and Cox regression model were applied to analyse the relationship between anxiety/depression and IBD-related poor outcomes, which were defined as urgent IBD-related hospitalization, IBD-related surgery, or death. Results: A total of 325 IBD patients were enrolled, 118 of whom were treated with corticosteroids, 88 with azathioprine/6-mercaptopurine (AZA/6-MP), and 147 with anti-TNF agents. Anxiety/depression symptoms were found to be significantly related to steroid resistance, but independent of AZA/6-MP and anti-TNF agents nonresponse. There was a significant association between anxiety/depression symptoms and IBD-related poor outcomes. Coexisting with anxiety/depression symptoms was an independent influencing factor of steroid resistance and IBD-related poor outcomes. Conclusion: IBD patients with anxiety/depression symptoms were at a higher risk of developing steroid resistance and IBD-related poor outcomes. Future studies are needed to explore whether interventions for anxiety and depression will improve their response to medications and change their prognosis.